Inhibition of macromolecular synthesis in cultured macrophages by Pseudomonas pseudomallei exotoxin - Mohamed, Rahmah; Nathan, Sheila; Embi, Noor; Razak, Nyonya; Ismail, Ghazally (John Wiley & Sons, 1989)
Pseudornonas pseudomallei exotoxin was found to be a potent inhibitor of protein and DNA synthesis in cultured macrophages. Inhibition of DNA synthesis occurred at toxin concentrations as low as 1–2 μg/ml and inhibition of 3H~thymidine uptake was almost complete at concentrations of 8 μgjml or more. A close correlation between cell damage and inhibition by DNA synthesis was observed. For protein synthesis, inhibition was obtained at much lower doses (0.06-2.0 μg/ml) of the toxin. At similar toxin concentrations, DNA synthesis was marginally affected. Further, it was shown that protein synthesis inhibition occurred almost immediately after incubation, reaching its maximal inhibitory effect of 70% after 6 hr. DNA synthesis, however, was minimally affected by a similar toxin concentration even after 10 hr of incubation. The inhibition of macromolecular synthesis in macrophages by P. pseudomallei exotoxin may be relevant to its modulatory effect on the host defense mechanism.